The Effect of Sleep Restriction, With or Without Exercise, on Skeletal Muscle Transcriptomic Profiles in Healthy Young Males - Lin, Wentao; Saner, Nicholas J.; Weng, Xiquan; Caruana, Nikeisha J.; Botella, Javier; Kuang, Jujiao; Lee, Matthew J-C.; Jamnick, Nicholas A.; Pitchford, Nathan W.; Garnham, Andrew; Bartlett, Jonathan D.; Chen, Hao; et al. (Frontiers in Endocrinology, 2022)
Background: Inadequate sleep is associated with many detrimental health effects, including increased risk of developing insulin resistance and type 2 diabetes. These effects are associated with changes to the skeletal muscle transcriptome, although this has not been characterised in response to a period of sleep restriction. Exercise induces a beneficial transcriptional response within skeletal muscle that may counteract some of the negative effects associated with sleep restriction. Methods: 20 healthy young males were allocated to one of three experimental groups: a Normal Sleep (NS) group (8 h time in bed (TIB) per night, for five nights), a Sleep Restriction (SR) group (4 h TIB per night, for five nights), and a Sleep Restriction and Exercise group (SR+EX) (4 h TIB per night, for five nights and three high-intensity interval exercise (HIIE) sessions). RNA sequencing was performed on muscle samples collected pre- and post-intervention. Our data was then compared to skeletal muscle transcriptomic data previously reported following sleep deprivation (24 h without sleep). Results: Gene set enrichment analysis (GSEA) indicated there was a decrease in enrichment of mitochondrial-related pathways and increased enrichment of inflammatory and immune response related pathways in the SR group post-intervention. However, the direction of enrichment in these same pathways was reversed in the SR+EX group. Despite this, there were no significant changes at the individual gene level from pre- to post-intervention. A set of genes previously shown to be decreased with sleep deprivation was also decreased in the SR group, but increased in the SR+EX group. Conclusion: The alterations to mitochondrial, inflammatory, and immune related pathways in skeletal muscle, following five nights of sleep restriction, provide insight regarding the transcriptional changes that underpin the detrimental effects associated with sleep loss. Performing three sessions of HIIE during sleep restriction reversed many of these transcriptional changes. Overall, the transcriptional alterations observed with a moderate period of sleep restriction were less evident than previously reported changes following a period of sleep deprivation.